Differential North Atlantic control of winter hydroclimate in late Holocene varved sediments of Lake Kortejärvi, eastern Finland. (30th March 2018) - Czymzik, Markus; Haltia, Eeva; Saarni, Saija; Saarinen, Timo; Brauer, Achim
Abstract : Sediment microfacies, geochemical μ‐XRF and X‐ray density analyses were conducted on varved sediments from Lake Kortejärvi (eastern Finland) covering the last 2700 years. The varves comprise couplets of detrital and organic sub‐layers throughout the complete time‐span. Based on their microfacies and stratigraphical position within a varve as well as comparisons with local discharge and meteorological data, thicker detrital layers are interpreted to reflect intensified snow‐melt floods following more humid winters. Detailed comparisons with monthly to annually resolved North Atlantic Oscillation (NAO) indices back to AD 1049 (901 a BP) suggest that multidecadal increases in snow‐melt layer thickness tend to be connected with a more positive phase of the NAO and, consequently, warmer winters. In contrast, distinct centennial intervals of thicker snow‐melt layers from −40 to 170, 280 to 460 and 1900 to 2300 a BP as well as around 2600 a BP do not consistently correspond to a particular NAO phase, but coincide with extended sea‐ice margins and a colder North Atlantic climate, causing intensified and southward shifted westerly cyclones. Our results point to a differential modification of North Atlantic winter hydroclimate working on varying time scales.